Development of Innovative Pharmaceuticals, Cosmetics, and Biologically Active Supplements, and Ensuring Their Quality (Herald of the National Children's Medical Center, 2025)
Development of innovative products in the fields of pharmaceuticals, cosmetics, and biologically active supplements; evaluation of their efficacy and safety; and scientific justification of control methods in compliance with international quality standards.
Keywords: Innovative pharmaceuticals; cosmetics; biologically active supplements; quality control; new technologies; pharmacology